Analisis persepsi dosen terhadap perbankan syariah (Studi kasus dosen tamu Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN SU) - Tri Inda Fadhila Rahma Inda (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2020)
Perception is the process of one’s interpretation of the environment, in this case the perception of Islamic banking. The purpose of this study was to determine how the perception of guest lecturers of Islamc Banking Study of Economic and Islamic Business UIN SU towards Islamic Banking. The method used is a qualitative method. The data uses are questionnaire and interview data. The results of study present data that 73,33% agree with the principles of Islamic banking. That is they have a good perception of the principles of Islamic banking, namely; Islamic banks are banks based on monotheism, guided by the Qur'an and hadith. Islamic Banks are banks that are free from usury, maysir and gharar. Sharia Banking in its business activities is based on sharia principles, economic democracy and prudential principles. 43% stated neutral on islamic bank operation. It means that the informants were still hesitant about the operations of islamic banks, because according to them islamic banks were still unable to operate in accordance with islamic principles, did not provide a large profit share to their customers, their products were difficult to access and the amount of administrative costs. 44% of informants agreed with the objectives of islamic banking. That is, informan have a good perception ofthe objectives of islamic banks, namely for the benefit. Islamic banks prioritize justice and togetherness for all their customers, islamic banks also contribute to reducing poverty through financing products. If seen from the aspect of general perception regarding the existance of islamic banks, islamic bank services, convenience and security in transactions, it can be concluded that 70% of informants have a good perception of islamic banks. The decicion of the informant in choosing an islamic bank, amounting to 70%.